Cutaneous manifestations of inflammatory bowel disease: basic characteristics, therapy, and potential pathophysiological associations - He, Ronghua; Zhao, Subei; Cui, Mingyu; Chen, Yanhao; Ma, Jinrong; Li, Jintao; Wang, Xiaodong (Frontiers in Immunology, 2023)
Inflammatory bowel disease (IBD) is a chronic inflammatory disease typically involving the gastrointestinal tract but not limited to it. IBD can be subdivided into Crohn's disease (CD) and ulcerative colitis (UC). Extraintestinal manifestations (EIMs) are observed in up to 47% of patients with IBD, with the most frequent reports of cutaneous manifestations. Among these, pyoderma gangrenosum (PG) and erythema nodosum (EN) are the two most common skin manifestations in IBD, and both are immune-related inflammatory skin diseases. The presence of cutaneous EIMs may either be concordant with intestinal disease activity or have an independent course. Despite some progress in research on EIMs, for instance, ectopic expression of gut-specific mucosal address cell adhesion molecule-1 (MAdCAM-1) and chemokine CCL25 on the vascular endothelium of the portal tract have been demonstrated in IBD-related primary sclerosing cholangitis (PSC), little is understood about the potential pathophysiological associations between IBD and cutaneous EIMs.Whether cutaneous EIMs are inflammatory events with a commonly shared genetic background or environmental risk factors with IBD but independent of IBD or are the result of an extraintestinal extension of intestinal inflammation, remains unclear. The review aims to we provide an overview of the two most representative cutaneous manifestations of IBD, describe IBD's epidemiology, clinical characteristics, and histology, and discuss the immunopathophysiology and existing treatment strategies with biologic agents, with a focus on the potential pathophysiological associations between IBD and cutaneous EIMs.